Reproductive politics and parental economies in Titus Andronicus - Burzyńska, Katarzyna (Studia Anglica Posnaniensia, 2023)
Tamora, Queen of the Goths in Shakespeare’s Titus Andronicus (1594), belongs to a relatively substantial canon of pregnant characters in English early modern drama. Her pregnant embodiment has generated less critical interest than the pregnancies and maternities of later tragic heroines. In this paper I wish to reread Tamora’s non-normative pregnancy and her maternal authority against a tenuously established consensus on reproduction and maternity in the period. Thus, my primary aim is to trace Tamora’s monstrous gestational body as a locus of the discursive triangularity of gender, race, and reproduction. Tamora is a devoted and passionate mother to her adult sons but her mothering is complicated by her pregnancy and a problematic child product, a result of her relationship with Aaron. I wish to look at Tamora’s pregnancy in conjunction with her maternal practices, albeit keeping the gestational experience as distinct and separate from her motherhood. Tamora’s pregnant embodiment is further complicated by the birthing ritual glimpsed in the play. I argue that by materializing the dreaded fruit of miscegenation in and through the reproductive body, the play demonstrates the threatening porosity of the emerging gender-race system. By circumventing maternal authority, the play also unveils the vulnerability of the supposedly sacrosanct, female-exclusive ritual to external male violations. Rather than confirming the ritual’s universality, the play problematizes maternal and paternal authority at the backdrop of deep-seated fears of racial bodily difference.